2021
DOI: 10.1002/ehf2.13442
|View full text |Cite
|
Sign up to set email alerts
|

Restricted left atrial dilatation can visually differentiate cardiac amyloidosis from hypertrophic cardiomyopathy

Abstract: Aims Cardiac amyloidosis (CA) is an infiltrative myocardial disease that occasionally mimics hypertrophic cardiomyopathy (HCM). The aim of this study is to investigate the discriminatory ability of visual assessment of left atrial (LA) function between CA and HCM on echocardiography. Methods and results In total, 93 patients with cardiac magnetic resonance imaging (CMR)-confirmed HCM and 34 with cardiac biopsy-confirmed CA were retrospectively assessed. LA dilatation was assessed via echocardiography in an api… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Recently, we demonstrated the usefulness of visual assessment of the left atrium to differentiate cardiac amyloidosis from hypertrophic cardiomyopathy [ 76 ]. As shown in Figure 4 , we classified the LA dilatation motion into three grades (preserved: grade 1, abnormal: grade 2, and restricted: grade 3) based on the apical four-chamber view and defined it as the LA dilatation grade (Inoue grade).…”
Section: Left Atrial Function In Cardiac Amyloidosismentioning
confidence: 99%
“…Recently, we demonstrated the usefulness of visual assessment of the left atrium to differentiate cardiac amyloidosis from hypertrophic cardiomyopathy [ 76 ]. As shown in Figure 4 , we classified the LA dilatation motion into three grades (preserved: grade 1, abnormal: grade 2, and restricted: grade 3) based on the apical four-chamber view and defined it as the LA dilatation grade (Inoue grade).…”
Section: Left Atrial Function In Cardiac Amyloidosismentioning
confidence: 99%
“…Impairment of nearly all functional phases for left and right atrial longitudinal strain appears to be a further valuable discriminative characteristic contributing towards diagnostic accuracy, as previously observed for the left atrium [ 11 ]. Additionally, visual characteristics such as atrial enlargement, interatrial septal thickening and atrial dysfunction are generally associated with CA rather than HCM phenotype [ 14 ]. These morphological differences appear to be associated with greater atrial strain impairment in CA patients compared to HCM patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent investigations have shown that cardiac strain provides discriminative value for all cardiac chambers and thus may support differentiation of CA from hypertrophic cardiomyopathy (HCM) and healthy control subjects (CTRL) [ 6 , 11 , 12 , 13 , 14 , 15 ]. Based on previous observations [ 11 , 12 , 14 , 15 , 16 ] and in the hope of optimizing CMR diagnostic accuracy for CA detection, we hypothesize that strain measurements of the diagnostically less popular cardiac chambers along with general cardiac functional parameters may achieve a high CA diagnostic accuracy. Cardiac strain parameters would thus solely derive from both atria and the right ventricle.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical utility of MRI-attained LA strain has experienced extensive growth in its diagnostic value. For example, the challenge of distinguishing between hypertrophic cardiomyopathy from cardiac amyloidosis 6 , 26 , 27 or even the differentiation between subtypes of amyloidosis 24 were shown to be facilitated through left atrial strain quantification. The majority of previous studies were performed using echocardiography, whereby MRI data still remains limited and partially inconsistent, particularly regarding specific parameter dependencies (e.g.…”
Section: Discussionmentioning
confidence: 99%